Beyond Objectivity-Bias Dichotomy: Media Framing as Soft Power Mechanism in International Conflict - Ainani, Muhammad; Yudiansyah, Faza (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2025)
Media framing of international conflicts significantly influences public perception and foreign policy discourse, as in the Israel-Lebanon conflict. The study examines how the attack on Lebanon by Israel in September to October 2024 was reported differently by Kompas.id (Indonesian secular), Republika.co.id (Indonesian Islamic), CNN.com (US mainstream), and Aljazeera.com (Qatari pan-Arab). It aims to understand how geographical location, ideology, and cultural context shape international conflict narratives. A qualitative framing analysis was performed using Robert M. Entman’s four-element structure: defining the problem, explaining the causes, judging the morality, and suggesting solutions. Four news articles were analyzed using a systematic coding process, and intercoder reliability was checked. Kompas.id used neutral language, highlighting the international community’s disapproval and refraining from taking sides. Republika.co.id presented Israel’s actions as violations of sovereignty and urged the international community to put pressure on the country. CNN.com gave equal attention to regional events and different viewpoints. Aljazeera.com highlighted the crisis and the violations of international law in a very critical way. Media framing operates as a soft power mechanism in international relations, constructing epistemological frameworks that transcend simple objectivity-bias dichotomies. Indonesian media balances Western ideas of neutrality and the need to support their region. It is important to understand these framing dynamics for media literacy, diplomatic strategy and to notice the variety of knowledge in international journalism. Future research should incorporate audience reception studies and examine longer-term framing patterns across multiple conflicts.